Strategi Mengatasi Kemacetan Lalu Lintas Melalui Surabaya Intelligent Transport System (SITS) dengan Pendekatan SOAR - Nurshabrina, Adita; Arif, Lukman (Policy, Law and Political Research Center, 2025)
Surabaya City for 2 consecutive years still occupies the top position as the most congested city in Indonesia. INRIXI in the 2021 Global Traffic report named Surabaya as the most congested city in Indonesia in 2021. This study aims to analyze and describe strategies to overcome traffic congestion through the Surabaya Intelligent Transport System (SITS) with the SOAR approach. The research approach uses a descriptive qualitative approach with primary and secondary data sources. Research informants were determined using the snowball sampling technique. The results of the study indicate that the SITS innovation has a positive impact on the community by helping to quickly reduce congestion by conveying accurate traffic information. SITS also supports Dishut operations in monitoring traffic through CCTV. Collaboration with Polantas and Radio Suara Surabaya also strengthens the traffic management strategy, so that SITS is considered effective in improving driving order and reducing accidents.